Aktivitasi Belajar Siswa Dengan Penggunaan Strategi Belajar Mind Map - Yenni Khairani Lubis; Eni Sumanti Nasution; Kasmawati Kasmawati (Institut Agama Islam Negeri Padangsidimpuan, 2022)
This study aims to produce an increase in student learning activities through the use of mind map learning strategies for class IX-4 students of SMP Negeri 8 Padangsidimpuan in the 2021-2022 academic year. The subjects of this study were students of class IX-4 SMP Negeri 8 Padangsidimpuan, totaling 30 people. This type of research is classroom action research (CAR) with the application of a Mind Map. The parameters observed were limited to: student activities during learning, the results of students' psychomotor abilities in making mind maps and student responses to mind map learning activities obtained after learning activities. The data obtained were analyzed by the percentage of value acquisition with descriptive and qualitative descriptive techniques. The results showed that in the first cycle the percentage of all activities was 51.79%, while in the second cycle the percentage of all activities was 72.07%, an increase of 20.28%. The results of the Mind Map assessment in the first cycle showed a percentage value of 69.3% or sufficient. Meanwhile, in Cycle II, the percentage value of 80.3% or good increased by 11% from Cycle I. Student responses to learning with the mind map learning strategy were very positive. Based on the results of the research above, it can be concluded that learning using mind map learning strategies on ecosystem materials in class IX-4 has increased from cycle I to cycle II.